Conjugate Electrospun 3D Gelatin Nanofiber Sponge for Rapid Hemostasis. Issue 20 (8th July 2021) - Xie, Xianrui; Li, Dan; Chen, Yujie; Shen, Yihong; Yu, Fan; Wang, Wei; Yuan, Zhengchao; Morsi, Yosry; Wu, Jinglei; Mo, Xiumei
Abstract: Developing an excellent hemostatic material with good biocompatibility and high blood absorption capacity for rapid hemostasis of deep non‐compressible hemorrhage remains a significant challenge. Herein, a novel conjugate electrospinning strategy to prepare an ultralight 3D gelatin sponge consisting of continuous interconnected nanofibers. This unique fluffy nanofiber structure endows the sponge with low density, high surface area, compressibility, and ultrastrong liquid absorption capacity. In vitro assessments show the gelatin nanofiber sponge has good cytocompatibility, high cell permeability, and low hemolysis ratio. The rat subcutaneous implantation studies demonstrate good biocompatibility and biodegradability of gelatin nanofiber sponge. Gelatin nanofiber sponge aggregates and activates platelets in large quantities to accelerate the formation of platelet embolism, and simultaneously escalates other extrinsic and intrinsic coagulation pathways, which collectively contribute to its superior hemostatic capacity. In vivo studies on an ear artery injury model and a liver trauma model of rabbits demonstrate that the gelatin nanofiber sponge rapidly induce stable blood clots with least blood loss compared to gelatin nanofiber membrane, medical gauze, and commercial gelatin hemostatic sponge. Hence, the gelatin nanofiber sponge holds great potential as an absorbable hemostatic agent for rapid hemostasis. Abstract : This work reports a novel conjugate electrospinning strategy to prepare an ultralight 3D nanofibers sponge. This fluffy nanofiber structure endows the sponge with low density, high surface area, compressibility, macroporous. This method can be widely applicable to the preparation of various polymer nanofiber sponges. The obtained gelatin nanofiber sponge holds great potential as an absorbable hemostatic agent for rapid hemostasis.